Psychosocial Profile Of Subjects Presenting With Sexual Dysfunctions In Psychiatry Outpatient Department Of A Teaching Hospital In Nepal (Journal of Psychiatrists' Association of Nepal, 2021)
Introduction: Sexuality is way people experience and express themselves sexually. It influences psychological, physical and social well-being of both men and women. Sexual dysfunctions are believed to be among the commonly prevalent psychological disorders in the general population but there is a lack of published research papers and literature related to sexuality and sexual medicine from Nepal. The aim of the present study was to descriptively analyze the nature of sexual dysfunctions in a teaching hospital.Material And Method: Retrospective analysis of data from subjects attending the psychiatry outpatient department in Nepalgunj Medical College Teaching Hospital, Kohalpur over the calendar year 2019 was done. Sociodemographic and clinical parameters of the subjects were obtained from the OPD register. Diagnosis was made using the DSM-5.Results: Out of total 54 subjects, 92.6% were male while 7.4% were female. Married subjects constituted 79.6% while single/unmarried 20.4%. Premature ejaculation was the most common sexual dysfunction encountered (55.5%) followed by erectile disorder (33.3%) and female sexual interest/arousal disorder (5.5%). Male hypoactive sexual desire disorder was seen in 3.7% and genito-pelvic pain/penetration disorder was seen in 2%.Conclusion: Males more commonly seek medical help for sexual dysfunction than females. People especially females, hesitate to discuss and seek medical help for sexual dysfunctions. There is lack of research on sexual medicine and sexuality from Nepal and prevalence of various sexual dysfunctions is not known.